Utilization and tolerance of beta-blockers among patients with AL amyloidosis. (2nd January 2022) - Briasoulis, Alexandros; Stamatelopoulos, Kimon; Petropoulos, Ioannis; Patras, Raphael; Theodorakakou, Foteini; Gavriatopoulou, Maria; Ntalianis, Argyrios; Dimopoulos, Meletios-Athanasios; Kastritis, Efstathios
Abstract: Background: The utilization and clinical impact of beta-blockers (BBs) in cardiac amyloidosis (CA) is largely unexplored. Methods: We conducted a retrospective, single-center analysis of indications, timing of initiation, types and doses of BB used, reasons to discontinue BB and association between BB tolerance and outcomes in a cohort of patients with immunoglobulin light chain amyloidosis (AL). Results: We reviewed 236 patients with AL CA and identified 53 patients taking BB (22.5%). Most patients presented in New York Heart Association Class (NYHA) II or III (74.5%) and 24% presented in Mayo stage IIIB. The most frequent indications for BB initiation were atrial fibrillation (AF) and coronary artery disease (CAD). In most cases (59%) BB was started before the diagnosis of CA. The median duration of BB treatment was 9 months (interquartile range [IQR] 3–24 months). Among patients receiving BB, 28 tolerated BB during follow-up whereas 25 patients discontinued BB. The main causes of BB discontinuation were hypotension and heart failure (HF) exacerbation. Patients intolerant to BB presented with more advanced NYHA class, worse performance status and lower median left ventricular ejection fraction (LVEF) at baseline. At median follow-up duration of 17.7 months, patients who did not tolerate BB had a poor survival. Conclusions: Although some patients with CA may have indications for treatment with BB, their use is uncommon and those with more advanced disease tolerate BB poorly. Intolerance to BB in patients with cardiac AL is an indicator of poorer outcome.